PENGABDIAN KEPADA MASYARAKAT PROMOSI INDUSTRI KERAJINAN TANGAN ANYAMAN BAMBU DI ERA PANDEMI COVID MENGGUNAKAN MEDIA SOSIAL INSTAGRAM PEKON GEMAHRIPAH (LP3K Lampung, 2021)
Marketing is the key to success in maintaining business continuity and competing with competitors of similar products. Makmur Sejati handicraft industry, Gemahripah Village, Pagelaran Subs-Distric Pringsewu District is a small to medium scale labor intensive industry that produces various forms of woven bamboo. Marketing of these industrial products is still limited in the surrounding Pringsewu region and is traditionally marketed through shops and word-of-mouth. The application of science and technology in the implementation of community service can provide solutions to problems of expanding marketing networks through the creation of social media. The results of sale on social media displays rate sale as 72%, which shows that the marketing partner's web page can be easily found by internet users through search engines.